Optimization in urban transport: an intermodal simulation with emphasis on energy efficiency - Bortolazzo, Shadia S. Assaf; Cavallazzi, Eugênio; Valente, Amir Mattar (Seven Editora, 2023)
In general, it can be said that patterns of energy production and consumption have been based on fossil fuels, which generate emissions of local pollutants; greenhouse gases (GHGs) and jeopardize the energy supply long-term on the planet. Concerning urban transport, Brazilian cities have developed with an emphasis on road transport. Thus, it is relevant to study energy efficiency in transport, to implement good solutions that meet the movements of users, and promote the efficient use of natural resources. This paper aims to estimate, on a network of fictitious transport, energy efficiency displacement of a given passenger demand using different modes of transport to measure the energy efficiency of the network. Specifically, we intend to verify and compare the energy consumption and carbon dioxide emissions in intermodal transport by rail modes - Light Rail (LRT) and bus - bus. The methodology was developed based on documentary and bibliographical research for data collection, and applied operations research techniques to assess the energy efficiency of the simulated network. The review includes the study of transport, its indispensability, and its influence on the environment. Energy efficiency in the transport matrix and the use of operations research as a support tool for optimization models are discussed. Finally, it observed that the modal integration, feeder system - distributor system - is an efficient solution as the energy consumption and GHG emissions. The methodology proved to be satisfactory and relevant and can be used for larger networks and real scenarios. As a continuation of this study is developing a methodological contribution to sustainable planning of urban passenger transport ( MPTS - URB ), which aims to estimate the monetary cost of energy efficiency from data on emissions and energy consumption by transport modes used in the transport network. DOI: https://doi.org/10.56238/methofocusinterv1-080